3D virtual museum design and navigation in VR - Wong, Johnathan (2019)
As Augmented Reality (AR) and Virtual Reality (VR) is gaining popularity in the world. The use of AR and VR technology allows users to immerse themselves into the virtual world locking out the physical world. The use of this technology is expanding out to numerous applications, one of which are museums and galleries. The idea of creating a VR gallery or museum that enables the user to take a non-restrictive virtual tour. This project is tasked to create an interactive 3D VR world of the Chinese Heritage Centre in Nanyang Technological University. The main objective of this project creates an interactive experience from the 3D model of the Chinese Heritage Centre (CHC). The virtual experience is to improve the user’s virtual visit by making exhibits and artifacts interactive. This interactive experience will be done in the Unity3D game engine paired with the SteamVR asset library in Unity. Users will be able to navigate the museum by using the HTC VIVE controller’s touchpad and take a self-guided tour. The virtual museum will show contents that exists in the museum.